Multiple thermochronometers applied to the quantitative analysis of compressive systems: the southern sub-Andean fold and thrust belt of Bolivia : From source rock to trap - Valdéz Hernández, Juan I.; Hernandez, Roberto M.; Farjat, Alejandra Dalenz; Cristallini, Ernesto O.; Alvarez, Luis A.; Dellmans, Luis M.; Costilla, Marcos R.; Alvarez, Andres F.; Becchio, Raúl; Bordese, Sofia; Arzadun, Guadalupe; Guibaldo, Cristina; et al. (Journal of South American earth sciences, 2021)
The evolution of fold and thrust belts requires time data restrictions to determine the rates related to the interaction of surface and subsurface processes and to quantify the time relationship between the components of the petroleum system: reservoir, seal, source rock and trap. The sub-Andean fold-and-thrust belt in the Bolivian territory in general, and the regional transect that links the structures of Curuyuqui-Carohuaicho-Tatarenda-Borebigua-Charagua and Mandeyapecua in particular, constitutes a complex multi-variable system in which the definition of time-Temperature (t-T) trajectories has led to new suitable structural and stratigraphic conclusions. The integration of multiple thermochronological-geochronological systems (Apatite Fission Track, Apatite (U-Th-Sm)/He and UPb SHRIMP on zircon) and the existing surface and subsurface geological constraints made it possible to develop a chrono-kinematic characterization of fault-related anticlines, defining their formation chronology, structural growth rate and link between them in the study area. Furthermore, it was also possible to perform a quantitative analysis of the subsidence-burial and exhumation-erosion phenomena that occurred from the deposition of Silurian-Devonian source rocks to the present time, providing relevant determinations to the modeling of the Oil & Gas system.